Novel polar biomarkers of the Miocene Maritza-East lignite, Bulgaria. (June 2016) - Stefanova, Maya; Simoneit, Bernd R.T.; Marinov, Stefan P.; Zdravkov, Alexander; Kortenski, Jordan
Highlights: Further insight into the composition of polar constituents in low rank coals. New polar diterpenoids in coal/clay extracts are identified and depth correlated. Cupressaceae / Taxodiaceae or Podocarpaceae are dominant palaeoflora. Chamaecydins confirm the existence of the Cupressaceae sensu lato ( s.l. ) family. Polar lupane structures indicate Betulaceae deciduous vegetation in palaeoflora. Abstract: The present study provides further insight into the composition of polar compounds in the Miocene Maritza-East lignite, Bulgaria. Samples from two coal seams and interbedded claystone layers have been analyzed by geochemical proxies for polar constituents, consisting of n -alkan-2-ones, n -alkanols, n -alkanoic acids, polar sesqui-, di-, and triterpenoids, steroids, hopanoid acids, etc. These series are quantified, correlated vs. depth, and various ratios calculated. Polar diterpenoids predominate in the soluble organic matter. Several new compounds were identified, i.e. 7, 11-dehydro-12-oxoabieta-7, 9(11), 13-triene, salvinolone, and chamaecydins. The preferential contribution of Cupressaceae / Taxodiaceae in the palaeoflora is confirmed by the significant abundance of polar diterpenoids (200–600 μg/g Corg ), and is further supported by the presence of chamaecydins (3–9 μg/g Corg ). The polar lupane assemblage attests that Betulaceae also was an important input from angiosperm vegetation to the palaeomire. The related new compounds are 24, 25-bisnoroxyallobetula-1, 3, 5(10)-triene and 24, 25-bisnorallobetula-1, 3, 5(10)-triene, which further support this point. This investigation increases the knowledge on floral progenitors and provides further proof of the input from the Cupressaceae / Taxodiaceae or Podocarpaceae families as the most abundant trees in the peat-forming environment of the Miocene Maritza-East Basin.